Problem-Based Learning Model Assisted by Guided LKPD: Experimentation in Mathematics Learning Exponential Materials - Mandey, Amelia Luisa; Mangobi, James U. L.; Kaunang, Derel F. (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Mathematics learning on exponential materials still faces various obstacles, especially regarding students' understanding of concepts and problem-solving skills. This can be seen from the low student learning outcomes and lack of active involvement in the learning process. The Problem-Based Learning (PBL) learning model is one approach that can stimulate students' high-level thinking in real-world problem-oriented situations, including learning how to learn. This study uses a quasi-experimental method with a pretest-posttest control group design. The subject of the survey was class X students of SMA Negeri 1 Ratahan, which was divided into two groups: an experimental class that applied the PBL model assisted by guided LKPD and a control class that used conventional learning. Guided LKPDs are designed to help students discover concepts through their activities and provide hands-on experience. The results show that the application of the guided LKPD-assisted PBL model has a positive influence on student learning outcomes. This is evidenced by the increase in the average score of the experimental class, which is higher than that of the control class. The PBL model also encourages students to be actively involved in problem-solving, think critically, and develop independent learning skills. Applying the Problem-Based Learning model assisted by guided LKPD effectively improves student learning outcomes in exponential materials. This learning model helps students understand mathematical concepts and develops higher-order thinking skills and problem-solving abilities. This study recommends using the PBL model assisted by guided LKPD as an effective alternative to mathematics learning.